ASSESSMENT OF SOCIAL MEDIA’S INFLUENCE ON THE ACADEMIC PERFORMANCE OF TERTIARY INSTITUTION STUDENT - Ddungu, Racheal Mugabi; Nakijoba, Rosemary; Awobamise, Ayodeji; Merab, Ariokot (Annals of Spiru Haret University. Economic Series, 2021)
This paper assesses the influence of social media on academic performance of tertiary institutions. The study made use of a quantitative approach where 100 questionnaires were distributed to tertiary institutions students in Ekiti State. The study findings reveal that all the respondents have access to the internet and that they do so through different mediums such as smart phones, tablets and computers. Also, smart phones are the most popular means of accessing the internet by students. These devices are portable and allow students to carry it along at any given time. Findings of this study reveal that Ekiti State University students spend more time on social media than reading their books, this makes them rely on social media to do their assignments without consulting other sources. The study also revealed that students’ exposure to social media has effect on their academic performance and that effect is negative. It is the perspective of this paper that undergraduate who invest more energy in online networking are liable to perform inadequately in their scholarly exercises than the individuals who don’t, because of an extraordinary number of times spent on long range informal communication exercises, the scholastic execution of undergraduates endure misfortunes which could prompt poor execution in their studies.